Evaluación del efecto de la homeopatía en la etapa inicial de desarrollo de plantas de tomate (Lycopersicum esculentum). - Ponce Meza, Brigitte Gabriela (2017)
The excessive use of agrochemicals within agriculture is called pollutant essentially chemical substances which are applied in the different stages of the crop both in germination, emergency, such as plant hormones. The present rescarch had as objective to evaluate the effect of different homeopathic treatments during the initial stage of development of tomato seedlings. The homeopathic medicines were used in tomato plants for a month under greenhouse conditions to observe the effect both in the germination stage and in the emergency stage. The rate and percentage of germination and emergence were determined to evaluate the effect of homeopathic medicines. Morphometric variables such as stem length, fresh biomass and dry weight were also evaluated. The effect of the homeopathic treatments significantly improved the rate and percentage of germination and emergencies, as well as the morphometric variables during the initial stage of development of tomato plants Lycopersicum esculentum The application of homeopathic medicines in the germination of the tomato seed there was a considerable improvement in all its characteristics demonstrating effectiveness at low concentrations both the homeopathic treatment Siliceous Terra 6C and Natrum muriaticum 12C which these played an important role from its percentage and germination rate to its total dry biomass Effect of Silica Terra 30C generated a positive effect on the emergence of tomato seedlings, improving plant height, as weight of fresh aerial biomass, fresh root biomass, aerial dry biomass. It was identified within the homeopathic products the best solution was both for germination stage Natrum muriaticum 6C and 12C while in the emergency stage the best solution was Silicea Terra 30C in tomato plants.